2021
DOI: 10.1088/1674-4527/21/2/47
|View full text |Cite
|
Sign up to set email alerts
|

The electromagnetic and gravitational-wave radiations of X-ray transient CDF-S XT2

Abstract: Binary neutron star (NS) mergers may result in remnants of supra-massive or even stable NS, which have been supported indirectly by observed X-ray plateau of some gamma-ray burst (GRB) afterglows. Recently, Xue et al. () discovered an X-ray transient CDF-S XT2 that is powered by a magnetar from merger of double NS via X-ray plateau and following stepper phase. However, the decay slope after the plateau emission is slightly larger than the theoretical value of spin-down in electromagnetic (EM) dominated by losi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…If all these four FXTs are magnetar-powered, then there is a question of whether the newly born magnetars in these systems are stable or not. Because their decays were all consistent with t −2 within 2σ, as expected for the spindown luminosity of a stable NS, it is more likely that a stable NS was formed in these systems (see however Lü et al 2021).…”
Section: Magnetar-powered X-ray Transientsmentioning
confidence: 62%
“…If all these four FXTs are magnetar-powered, then there is a question of whether the newly born magnetars in these systems are stable or not. Because their decays were all consistent with t −2 within 2σ, as expected for the spindown luminosity of a stable NS, it is more likely that a stable NS was formed in these systems (see however Lü et al 2021).…”
Section: Magnetar-powered X-ray Transientsmentioning
confidence: 62%
“…As discussed above, we only adopt one magnetar EOS to do the calculations. Now, to discuss the dependence of the GW radiation on the EOS, we consider 12 EOSs that are reported in the literature [62][63][64][65][66]. The relevant initial parameters we selected for different EOS are listed in Table I.…”
Section: Gw Radiation Evolution In a Magnetarmentioning
confidence: 99%
“…The black dotted line is the sensitivity limits for ET, and the black and gray solid lines are the sensitivity limits for aLIGO-Hanford and aLIGO-Livingston, respectively. The data of the noise curve are taken from Ref [66]…”
mentioning
confidence: 99%
“…These two FXTs were later studied in detail by Bauer et al (2017) and Xue et al (2019), respectively, and re-identified as FXTs 14 and 16 in Papers I and II, respectively. XRT 150322 is particularly intriguing because it exhibits a flat, extended X-ray light curve that suggests a magnetar-wind origin (Sun et al 2019;Xiao et al 2019;Lü et al 2019), similar to some SGRB X-ray afterglows (e.g., Rowlinson et al 2010Rowlinson et al , 2013Troja et al 2019).…”
Section: Introductionmentioning
confidence: 99%